2018
DOI: 10.1007/s10864-018-9292-0
|View full text |Cite
|
Sign up to set email alerts
|

Training Individuals to Implement Applied Behavior Analytic Procedures via Telehealth: A Systematic Review of the Literature

Abstract: The purpose of this article is to summarize literature relating to training individuals to implement applied behavior analytic procedures via telehealth and identify any gaps in the evidence base for this type of support. A systematic literature search revealed 20 articles focusing on training individuals to implement specific ABA techniques via telehealth. The Evaluative Method (Reichow et al. in J Austism Dev Disord 38:1311-1319; Reichow, in: Reichow, Doehring, Cicchetti, Volkmar (eds) Evidence-based practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
128
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 77 publications
7
128
1
1
Order By: Relevance
“…Our reported initiatives in on-demand telehealth parent training provide both a detailed guide on how to create such a parent training curriculum and preliminary evidence supporting the effectiveness of its different components to increase parental adherence, such as using non-behavior-analytic terms, incorporating a brief ACT session, and including a competence-based contingency. The current study is in line with previous research that suggests the utility of using a telehealth model in ABA services (Suess, Wacker, Schwartz, Lustig, & Detrick, 2016 ; Tomlinson et al, 2018 ). It extends the study by Vismara, McCormick, Young, Nadhan, and Monlux ( 2013 ), demonstrating the effectiveness of an ABA parent training program via remote consultation and self-guided learning platform.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our reported initiatives in on-demand telehealth parent training provide both a detailed guide on how to create such a parent training curriculum and preliminary evidence supporting the effectiveness of its different components to increase parental adherence, such as using non-behavior-analytic terms, incorporating a brief ACT session, and including a competence-based contingency. The current study is in line with previous research that suggests the utility of using a telehealth model in ABA services (Suess, Wacker, Schwartz, Lustig, & Detrick, 2016 ; Tomlinson et al, 2018 ). It extends the study by Vismara, McCormick, Young, Nadhan, and Monlux ( 2013 ), demonstrating the effectiveness of an ABA parent training program via remote consultation and self-guided learning platform.…”
Section: Discussionsupporting
confidence: 91%
“…However, most agencies are unfamiliar with the process of developing an ABA telehealth program from scratch, and there are a limited number of publications investigating different parameters in ABA telehealth models. Tomlinson, Gore, and McGill ( 2018 ) conducted an extensive literature review on this topic and identified 20 studies that utilized a telehealth model. Cumulatively, their findings suggested promising outcomes, as trainees were able to implement various behavior-analytic techniques (e.g., conduct preference assessments and functional analysis, implement differential reinforcement techniques, provide discrete-trial teaching) following the telehealth intervention (Fischer et al, 2016 ; Hay-Hansson & Eldevik, 2013 ; Higgins, Luczynski, Carroll, Fisher, & Mudford, 2017 ; Lindgren et al, 2016 ).…”
mentioning
confidence: 99%
“…As a result, the ratings for the primary quality indicator of participant characteristics could be coded either as high (if items i‐iii were included) or unacceptable (if any of items i‐iii were not included), with the acceptable category removed. Furthermore, Reichow et al's () original strength ratings had three categories, which were expanded to five ratings in the present review to produce a more sensitive quality assessment tool with a wider range of ratings (Tomlinson, Gore, & McGill, ). The adapted requirements for each strength rating are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Telehealth technologies provide a means for behavior analysts to disseminate behavior‐analytic services worldwide. Professionals in multiple studies have used video conferencing to deliver instructions, prompts, and feedback remotely while training caregivers and therapists to implement behavioral interventions with their children (e.g., Heitzman‐Powell, Buzhardt, Rusinko, & Miller, ; Machalicek et al, ; Vismara, McCormick, Young, Nadhan, & Monlux, ; Wainer & Ingersoll, ; see also Tomlinson, Gore, & McGill, , for a review). For example, practitioners have remotely coached parents of children with autism to conduct functional analyses (FAs) of problem behavior and to implement functional communication training (FCT) in their homes (e.g., Wacker et al, , ).…”
mentioning
confidence: 99%